Opportunities and Challenges in Implementing Cash Waqf in Climate Change Mitigation in West Lombok Regency - Ihsan Rois; Moh. Huzaini; Subhan Purwadinata; Ali Akbar Hidayat; Widyatul Jannah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Climate change has become a problem that threatens the entire world, and its impact is increasingly being felt in various regions, including the district of West Lombok. This region often experiences various natural disasters such as floods, droughts, and declining agricultural production due to climate change, which has an impact on the community's economy. This study aims to explore the opportunities and challenges of implementing cash waqf for climate change mitigation in West Lombok Regency. This study develops the concept of green waqf that can be used for forest rehabilitation, renewable energy, and sustainable natural resource management. The method used is qualitative research with literature studies, in-depth interviews with stakeholders, and analysis of secondary data related to the potential for waqf in the area. The results of the study show that the opportunities for implementing cash waqf are wide open for climate change mitigation in West Lombok. Meanwhile, the challenges faced are low public awareness of cash waqf, a limited number of cash waqf nazhir, and a limited number of cash waqf collection banks.